STRATEGI PEMBELAJARAN GURU DALAM MEMBENTUK KARAKTER ANAK SESUAI PROFIL PELAJAR PANCASILA DI TK IT AN-NAFIS TELUK MENGKUDU - Arfah Julia; Mawaddah Nst (CV. ADIBA ASIHA AMIRA, 2023)
This study aims to determine the extent to which the teacher's ability to shape the character of children according to the profile of Pancasila students. This type of research is descriptive qualitative. The subjects of this study were the principals and teachers of TK IT An-Nafis Teluk Mengkudu. The object of this research is to describe the teacher's ability to shape children's character according to the profile of Pancasila students. Data collection techniques were carried out by observation, interviews and documentation. The results of this study are that teachers are able to shape children's character according to the profile of Pancasila students. It must be multi-level and multi-channel because it is not possible only to be carried out by PAUD institutions, but also by families and communities. Character building requires exemplary, real behavior in authentic life settings and cannot be built instantly. Early childhood is a period of preparation for real school, so the formation of good character at an early age is a very important thing to do. Character building from an early age is very important so that children have a strong mentality when facing challenges, changes and certain situations in the future.